Studi Analisis Integrasi Nilai-Nilai Moderasi Beragama dalam Buku Ajar Pendidikan Agama Islam dan Budi Pekerti Kelas II Sekolah Dasar Edisi Revisi Tahun 2017 - Ulifah Azwarani Rochmah; Marno Marno (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
The rise of radicalism and extremism has recently prompted the Ministry of Religion to promote a program of religious moderation in every line of social life. In the field of education, for example, the values of religious moderation are integrated into certain subjects such as Islamic Religious Education and Moral Character. This research attempts to analyze the values of moderation that are integrated into the 2017 Revised Edition of PAI and Budi Pekerti textbooks for Class II SD. The data were obtained through a literature review from primary sources, namely textbooks, and secondary sources in the form of related literature as support. The results of the study show that the integration of religious moderation values in this PAI textbook covers all aspects, starting from core competencies, basic competencies, and subject matter. Strategies and approaches, picture illustrations, and evaluations contained in textbooks are also oriented towards forming an attitude of moderation in students. The research concludes that the values of moderation that are integrated in this textbook can be understood, and it would be better if they were refined again in the future.